(untitled) (Medicina y Seguridad del Trabajo, 2024)
Mental health problems in the workplace and their management are a social and economic priority with an unequal impact on individuals. Certain working conditions are associated with a higher prevalence. However, causality is an open debate that represents part of the exposome. Interventions in this area are a protective element and are mostly carried out on an individual basis, as compared to improving working conditions, work reorganisation or other mental health initiatives. However, mixed interventions with a holistic approach significantly reduce stress, anxiety, burnout and depression among the working population. In a world of work subject to digital, demographic, socio-economic and climatic transformation, the ILO 2024-2030, European 2021-2027 and Spanish 2023-2027 Occupational Safety and Health Strategies together with the European 2023 and Spanish 2022-2026 Mental Health Strategies assume a people-centred, holistic, collaborative, continuum of care, quality approach, applying evidence-based clinical practice guidelines and protocols. In this multidisciplinary task of occupational health in the face of mental health problems in companies as a result of the health crisis, the application of the standardized nursing language NANDA, NOC and NIC translates into a care plan aimed at achieving results adapted to people’s needs.